DE DIGNITATE HOMINIS. DE LA GIOVANNI PICO DELLA MIRANDOLA LA BLAISE PASCAL (Journal for Freedom of Conscience (Jurnalul Libertății de Conștiință), 2022)
De Dignitate Hominis – From Giovanni Pico della Mirandola to Blaise PascalDignity is the most often used concept because it refers to our human essence every time. Each person is concerned about his or her dignity because this is a natural right of each of us. The philosophical approach of this topic concerns some important philosophers like: Giovanni Pico della Mirandola who is the most important philosopher of the Renaissance, than there’s René Descartes who is called the father of the modern rationalism and Blaise Pascal who is well known for his theory of dualism.